Making Ideas Happen : Overcoming the obstacles between vision and reality - Belsky, Scott (2012)
According to Scott Belsky, the capacity to make ideas happen can be developed by anyone willing to develop their organisational habits and leadership capability. He has spent years studying creative people and teams that are especially productive.
Electronic version also available.